VD_FINDINFO HC / 2011 / 422 vom 9. Mai 2011 - VD Tribunal cantonal (2011)
DIVORCE, OBLIGATION D'ENTRETIEN, ENFANT | 138 al. 1 CC, 145 al. 1 CC, 276 CC, 285 al. 1 CC, 262 al. 2 CO, 374c CPC, 451 ch. 2 CPC, 452 al. 1ter CPC, 452 al. 2 CPC